APLIKASI GREEN ARCHITECTURE PADA RUMAH GEDONG - . Anisa (Universitas Negeri Yogyakarta, 2010)
ABSTRACTGreen architecture is a scheme process in lessening unfavourableenvironmental impact, increase comfort of man by increasing efficiency, and reductionof usage of resource, energy, usage of farm, and management of effective garbage inarchitecture level (Kwok Allison dalam Ming Kok, Cheah, 2008). This research result,that is found some element in houses gedong which are evidence green architecture.(1) vegetation optimalisation which form out of two yard at house gedong; (2) Themany building side which diekspos and mass configuraton in site; (3) Design fasadebuilding, possible to maximize natural atmosphere and illumination; (4) Terrace;coreand teritis. Terrace amounting to multiple and teritis the in all heat Create building sideto depend and don't coming into house; (5) Draught with crossed ventilation,presentation of from aperture in the form of door, window, roster and other aperture atpart of building wall.Keyword: Green architecture, rumah Gedong